Efektivitas Larvasida Kombinasi Daun Suren (Toona sureni) dan Jeruk Nipis (Citrus aurantiifolia) - Bestari, Rochmadina Suci; Hibatullah, Afif Iqbal; Santoso, Talitha Ulima; Rosyidah, Devi Usdiana; Sintowati, Retno; Kusumaningrum, Tanjung Anitasari Indah (Lembaga Penelitian dan Pengabdian Masyarakat Politeknik Muhammadiyah Makassar, 2024)
The use of Abate larvicide to control dengue vectors has been carried out for years, causing the mosquito population to become resistant and environmental degradation. Therefore, it is necessary to use alternative larvicides from biological plants. Suren leaves (Toona sureni) and lime leaves (Citrus aurantiifolia) contain active substances flavonoids, saponins and alkaloids which are useful for killing Aedes aegypti larvae. The aim of this research was to determine the effectiveness of combination of suren leaf and lime leaf extract in killing Aedes aegypti larvae. This research method is a true experiment with a post-test only control group design. Larvae were divided into 6 groups, namely positive control, negative control, P1 (suren leaf+lime leaves extract 0.5%), P2 (suren leaf+lime leaves extract 1%), P3 (suren leaf+lime leaves extract 1.5%). Each glass contains 25 larvae. The Kolmogorov Smirnov normality test was carried out with abnormal result, the homogeneity test with non-homogeneous results, and the Mann-Whitney test. The results obtained were 99% larval death in the 6th hour by the P3 group. The conclusion of this research is that the combination of suren leaf and lime extracts 0.5%, 1% and 1.5% is effective in killing Aedes aegypti larvae in the 6th hour exposure.